2006
DOI: 10.1007/s11284-006-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral manipulation of host caterpillars by the primary parasitoid waspCotesia glomerata(L.) to construct defensive webs against hyperparasitism

Abstract: Many parasitoids control the behavior of their hosts to achieve more preferable conditions. Decreasing predation pressure is a main aim of host manipulation. Some parasitoids control host behavior to escape from their enemies, whereas others manipulate hosts into constructing defensive structures as barriers against hyperparasitism. Larvae of the parasitoid wasp Cotesia glomerata form cocoon clusters after egression from the parasitized host caterpillar of the butterfly Pieris brassicae. After the egression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…Previous experiments examining the function of retaining the use of the dying caterpillar have generally argued that it acts as a 'bodyguard' against predators and/or hyperparasitoids (the 'usurpation hypothesis'; Brodeur & Vet, 1994;Tanaka & Ohsaki, 2006, 2009Grosman et al, 2008;Harvey et al, 2008aHarvey et al, ,b, 2011Maure et al, 2011). However, the level of physical activity exhibited by parasitized caterpillars varies dramatically from one host-parasitoid association to another.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments examining the function of retaining the use of the dying caterpillar have generally argued that it acts as a 'bodyguard' against predators and/or hyperparasitoids (the 'usurpation hypothesis'; Brodeur & Vet, 1994;Tanaka & Ohsaki, 2006, 2009Grosman et al, 2008;Harvey et al, 2008aHarvey et al, ,b, 2011Maure et al, 2011). However, the level of physical activity exhibited by parasitized caterpillars varies dramatically from one host-parasitoid association to another.…”
Section: Discussionmentioning
confidence: 99%
“…In combination, these enemies can greatly reduce populations of parasitoids in the field (H€ oller et al, 1993). The parasitoids produce cocoons that may be physically attached to the host dorsum (Kester & Jackson, 1996;Harvey et al, 2008a) or else are placed under or very close to the host (Tanaka & Ohsaki, 2006, 2009Grosman et al, 2008;Harvey et al, 2008bHarvey et al, , 2011. The parasitoids produce cocoons that may be physically attached to the host dorsum (Kester & Jackson, 1996;Harvey et al, 2008a) or else are placed under or very close to the host (Tanaka & Ohsaki, 2006, 2009Grosman et al, 2008;Harvey et al, 2008bHarvey et al, , 2011.…”
Section: Among the Most Famous Examples Of Induced Changes In Host Bementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that retaining the use of the surviving host as a "bodyguard" is an effective strategy against hyperparasitoids (Harvey et al 2008a,b) and predators (Kester andJackson 1996, Grosman et al 2008). However, the results of other studies have been less conclusive (Tanaka and Ohsaki 2006). A recent study also reported that M. pulchricornis cocoons that were suspended from threads suffered lower predation from ants than cocoons that were attached to the leaf surface (Shirai and Maeto 2007).…”
mentioning
confidence: 94%
“…They manipulate the behaviour as well as biochemical and physiological characteristics of their hosts (Fritz 1982;Brodeur and McNeil 1992;Eberhard 2000;Tanaka and Oshaki 2006) to improve their chances of survival.…”
Section: Introductionmentioning
confidence: 99%